2017
DOI: 10.15232/pas.2017-01642
|View full text |Cite
|
Sign up to set email alerts
|

A survey of recommended practices made by veterinary practitioners to cow-calf operations in the United States and Canada

Abstract: Practicing veterinarians (n = 148) who service commercial beef cow-calf herds responded to a survey describing general recommendations made to their clients in terms of vaccine protocol, health, and production practices. Responding veterinarians represented 35 states in the United States and 3 provinces in Canada. More than 50% of responding veterinarians devote over 50% of their practice to service commercial cow-calf producers. The largest group (33%) of veterinarians have been in practice for over 30 yr. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…14 As calf age increased (ie, preweaning vs postweaning), there was a slight increase in the percentage of veterinarians who recommended MLV vaccines versus killed virus vaccines (93% and 7%, respectively). 14 Although the preceding information is consistent with other vaccine recommendations 18 and reports, [19][20][21] where most veterinarians recommended routine administration of respiratory vaccines to beef calves, the USDA reported 9 that 60.6% of beef cow-calf operations (accounting for 30% of the US cattle population) did not vaccinate calves for respiratory disease from birth until the time they were sold. This discrepancy between veterinarian recommendation and producer implementation is concerning, given that 99% of veterinarians in the United States and Canada recommend some type of vaccination protocol at the cow-calf level of production.…”
Section: Current Vaccination Recommendationssupporting
confidence: 67%
See 4 more Smart Citations
“…14 As calf age increased (ie, preweaning vs postweaning), there was a slight increase in the percentage of veterinarians who recommended MLV vaccines versus killed virus vaccines (93% and 7%, respectively). 14 Although the preceding information is consistent with other vaccine recommendations 18 and reports, [19][20][21] where most veterinarians recommended routine administration of respiratory vaccines to beef calves, the USDA reported 9 that 60.6% of beef cow-calf operations (accounting for 30% of the US cattle population) did not vaccinate calves for respiratory disease from birth until the time they were sold. This discrepancy between veterinarian recommendation and producer implementation is concerning, given that 99% of veterinarians in the United States and Canada recommend some type of vaccination protocol at the cow-calf level of production.…”
Section: Current Vaccination Recommendationssupporting
confidence: 67%
“…Beef cow-calf operations and feedlots across North America are frequently provided vaccine recommendations from veterinary practitioners or other sources; however, a scarcity of literature exists that summarizes and reports these recommendations at the cow-calf level. 14 In contrast, several publications exist that describe recommendations and practices for vaccination and health management at the feedlot level. 12,15,16 Results from a US Department of Agriculture (USDA)-Animal and Plant Health Inspection Service survey 17 indicated that although vaccinating cattle is a relatively common practice in the cow-calf sector, it is not universally adopted, which leaves a significant portion of the US beef cattle population susceptible to numerous preventable diseases.…”
Section: Current Vaccination Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations